Google AdWords for dummies - Jacobson, Howie (--For dummies., 2009)
"Learn to: use the new free tools included in AdWords; work with the new interface and use website optimizer; manage your account with AdWords editor."--Cover page [1] Presents strategies for writing a successful Internet marketing campaign using Google AdWords